Long-term empirical monitoring indicates the tolerance of the giant panda habitat to climate change under contemporary conservation policies. (March 2020) - Li, Ting; Luo, Peng; Luo, Chuan; Yang, Hao; Li, Yuejiao; Zuo, Dandan; Xiong, Qinli; Mo, Li; Mu, Chengxiang; Gu, Xiaodong; Zhou, Shiqiang; Huang, Jinyan; et al.
Highlights: The giant panda habitat area has become warmer and drier in the past four decades. Plant community in giant panda habitat area has kept relatively stable. The abundance of the main food bamboo of giant panda has increased. Coordination changes of functional traits could mitigate climate change pressures. Abstract: Climate change has been predicted as a major threat to giant panda habitat. While modelling prediction of the impact of climate change on habitat quality may overlook or underestimate biological interactions and adaptations, long-term monitoring is therefore essential approach to see the real situation. We analyzed the changes in plant composition and structure of 107 long-term monitoring plots in the giant panda habitat over four decades, and found that 1) the climate has become warmer and drier in the overall giant panda habitat; 2) plant species richness, different functional groups and dominant trees species abundance have kept relatively stable without human interference, and plant community canopy has not changed significantly; 3) the abundance of the giant panda's main food, bamboo, has increased; 4) specific leaf area had a significant relationship with dominant plant species abundance over time, which implies that plant functional traits would be potential indicators of assessing the impacts of climate change on habitat quality. Our study suggests that threats of climate change to giant panda habitat might be mitigated by contemporary conservation, highlighting the importance long-term protection of the natural processes and the control of human disturbances in the conservation of giant panda and other endangered animal species.